The Essence of Rationality Concept in Contracting Islamic Economics Business - Wahyudi, Trubus (JURNAL AKTA, 2022)
This research aims to know the paradigm of sharia economic business contracting activities carried out by humans as God's caliphs on earth should be carried out in good faith and understand the concept of contractual rationality and the obligation to help each other in carrying out Islamic economic activities which aim, among other things, to worship Allah SWT. Humans are ordered to believe in the Day of Judgment, because all the behavior of human economic activities will be controlled and he is aware that all his actions will be held accountable later by Allah SWT. In the matter of contracting/agreements, Islam provides guidelines as stated in the letter Al Isra'(17) verse 34 which means: "And fulfill the promise, in fact the promise must be held accountable". The approach method used in this paper is the normative juridical approach. Normative juridical legal research is legal research carried out by examining the law legally as it is according to library materials or secondary data obtained and related to the material being studied. Secondary data is meant to collect data by means of library research in order to obtain a theoretical basis, which is grouped into 3 (three) legal materials, namely 1) primary legal materials, 2) Secondary legal materials. 3) Tertiary Legal Materials, namely legal materials that are supporting in nature to be able to provide instructions and explanations for primary and secondary legal materials. The purpose of discussing the article with the title Essence of the Concept of Rationality in Shari'ah economic business contracts is to reveal the very essence of how Islam provide a compass direction and solutions for various economic business contracting activities that are faced by humans in general, so that they get a handle on the boundaries of halal and haram related to the values contained in the teachings of Islam itself ; including the birth of a contract in a sharia economic business which is the main guide in contracting sharia economic business, therefore an actor in a sharia economic business contract must understand the concept of rationality in contracting sharia economic business, universally aiming to achieve mashlahah and or falah.